2006
DOI: 10.1128/jb.188.2.424-430.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an ABC Transporter Required for Iron Acquisition and Virulence inMycobacterium tuberculosis

Abstract: Iron availability affects the course of tuberculosis infection, and the ability to acquire this metal is known to be essential for replication of Mycobacterium tuberculosis in human macrophages. M. tuberculosis overcomes iron deficiency by producing siderophores. The relevance of siderophore synthesis for iron acquisition by M. tuberculosis has been demonstrated, but the molecules involved in iron uptake are currently unknown. We have identified two genes (irtA and irtB) encoding an ABC transporter similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
241
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(251 citation statements)
references
References 24 publications
7
241
1
2
Order By: Relevance
“…5). The ATP-binding cassette iron-regulated transporter IrtAB is involved in the uptake of cMBT across the inner membrane (29). Furthermore, as the N-terminal domain of IrtA binds flavin adenine dinucleotide (30), it was suggested that the iron in Fe-cMBT is reduced, as it is imported into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The ATP-binding cassette iron-regulated transporter IrtAB is involved in the uptake of cMBT across the inner membrane (29). Furthermore, as the N-terminal domain of IrtA binds flavin adenine dinucleotide (30), it was suggested that the iron in Fe-cMBT is reduced, as it is imported into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…and cMBT (Fe-cMBT) are acquired by Mtb by a process dependent on the ESX-3 secretion system (18, 47) (omitted for clarity) likely involving a siderophore receptor. Iron is dissociated from cMBT by IrtAB concomitant with its import (29,30). Iron is dissociated from MBT by a reductive process (31) at a yet-to-be-determined subcellular location.…”
Section: Methodsmentioning
confidence: 99%
“…Interessantemente, foi demonstrado que a ausência do gene IrtAB reduziu o processo de infecção pelo MTB. 97 Outro alvo potencial envolvido na obtenção de ferro inclui o EsX-3 e o sistema de sideróforos mmpS4/S5. 98 No entanto, não somente a obtenção como também o estoque de ferro é crucial para a sobrevivência do MTB.…”
Section: Alvos Envolvidos Com O Metabolismo Do Ferrounclassified
“…Transport through the Gram-negative outer membrane transporters occurs through specialized proteins associated with the TonB protein complex, which transduces energy from the cytoplasmic proton motive force (3,10,11). Inner membrane ATP-binding cassette transporters in both Gram-negative and Gram-positive organisms transport ferric siderophore complexes, or the iron released from them, to the cytoplasm (12)(13)(14)(15)(16). Once ferric siderophores are internalized, their intracellular fate varies between different siderophores, with reported examples of Fe(III) reduction to Fe(II) or Fe(III)-siderophore hydrolysis.…”
Section: Siderophoresmentioning
confidence: 99%
“…Once ferric siderophores are internalized, their intracellular fate varies between different siderophores, with reported examples of Fe(III) reduction to Fe(II) or Fe(III)-siderophore hydrolysis. All or part of the siderophore may be recycled and used again after releasing its metal ion cargo (2, 18).Although pathogens often carry multiple iron acquisition systems that are redundant in laboratory culture conditions, siderophore-dependent systems appear to play specialized roles at the host-pathogen interface (2,16,19,20). Specifically, siderophores have been ascribed roles in liberating ferric ions bound to host iron storage proteins or sequestered away from pathogens within distinctive compartments.…”
mentioning
confidence: 99%